Pengenalan Pangan Sehat untuk Anak Usia Dini Melalui Aktivitas Kreatif Membuat Puding Pisang di Kabupaten Alor, Nusa Tenggara Timur - Anita Trisia Dimu Lobo; Solfina Mauleti (ABDIMAS : Jurnal Pengabdian Masyarakat, 2026)
The introduction of healthy eating habits from an early age is a crucial step in building a healthy and intelligent generation. This study aims to introduce the concept of healthy food to early childhood through practical activities, specifically making banana pudding. Conducted in Alor Regency, East Nusa Tenggara, this research involved preschool-aged children. The activity was designed to provide a fun learning experience while fostering a basic understanding of the benefits of fruits, especially bananas, as part of a healthy diet. The research results show that this creative, activity-based approach effectively increases children's interest in healthy foods. Furthermore, family involvement in the activity contributes to creating an environment that supports healthy eating habits.